Immunogenicity and reactogenicity of ten-valent versus 13-valent pneumococcal conjugate vaccines among infants in Ho Chi Minh City, Vietnam: a randomised controlled trial. Issue 5 (May 2019) - Temple, Beth; Toan, Nguyen Trong; Dai, Vo Thi Trang; Bright, Kathryn; Licciardi, Paul Vincent; Marimla, Rachel Ann; Nguyen, Cattram Duong; Uyen, Doan Y; Balloch, Anne; Huu, Tran Ngoc; Mulholland, Edward Kim
Summary: Background: Few data are available to support the choice between the two currently available pneumococcal conjugate vaccines (PCVs), ten-valent PCV (PCV10) and 13-valent PCV (PCV13). Here we report a head-to-head comparison of the immunogenicity and reactogenicity of PCV10 and PCV13. Methods: In this parallel, open-label, randomised controlled trial, healthy infants from two districts in Ho Chi Minh City, Vietnam, were randomly allocated (in a 3:3:5:4:5:4 ratio), with use of a computer-generated list, to one of six infant PCV schedules: PCV10 in a 3 + 1 (group A), 3 + 0 (group B), 2 + 1 (group C), or two-dose schedule (group D); PCV13 in a 2 + 1 schedule (group E); or no infant PCV (control; group F). Blood samples were collected from infants between 2 months and 18 months of age at various timepoints before and after PCV doses and analysed (in a blinded manner) by ELISA and opsonophagocytic assay. The trial had two independent aims: to compare vaccination responses between PCV10 and PCV13, and to evaluate different schedules of PCV10. In this Article, we present results pertaining to the first aim. The primary outcome was the proportion of infants with an IgG concentration of at least 0·35 μg/mL for the ten serotypes common to the two vaccines at age 5 months, 4 weeks after the two-dose primary vaccination series (group C vs group E, per protocol population). An overall difference among the schedules was defined as at least seven of ten serotypes differing in the same direction at the 10% level. We also assessed whether the two-dose primary series of PCV13 (group E) was non-inferior at the 10% level to a three-dose primary series of PCV10 (groups A and B). This trial is registered withClinicalTrials.gov, numberNCT01953510 . Findings: Of 1424 infants screened between Sept 30, 2013, and Jan 9, 2015, 1201 were allocated to the six groups: 152 (13%) to group A, 149 (12%) to group B, 250 (21%) to group C, 202 (17%) to group D, 251 (21%) to group E, and 197 (16%) to group F. 237 (95%) participants in group C (PCV10) and 232 (92%) in group E (PCV13) completed the primary vaccination series and had blood draws within the specified window at age 5 months, at which time the proportion of infants with IgG concentrations of at least 0·35 μg/mL did not differ between groups at the 10% level for any serotype (PCV10–PCV13 risk difference −2·1% [95% CI −4·8 to −0·1] for serotype 1; −1·3% [–3·7 to 0·6] for serotype 4; −3·4% [–6·8 to −0·4] for serotype 5; 15·6 [7·2 to 23·7] for serotype 6B; −1·3% [–3·7 to 0·6] for serotype 7F; −1·6% [–5·1 to 1·7] for serotype 9V; 0·0% [–2·7 to 2·9] for serotype 14; −2·1% [–5·3 to 0·9] for serotype 18C; 0·0% [–2·2 to 2·3] for serotype 19F; and −11·6% [–18·2 to −4·9] for serotype 23F). At the same timepoint, two doses of PCV13 were non-inferior to three doses of PCV10 for nine of the ten shared serotypes (excluding 6B). Reactogenicity and serious adverse events were monitored according to good clinical practice guidelines, and the profiles were similar in the two groups. Interpretation: PCV10 and PCV13 are similarly highly immunogenic when used in 2 + 1 schedule. The choice of vaccine might be influenced by factors such as the comparative magnitude of the antibody responses, price, and the relative importance of different serotypes in different settings. Funding: National Health and Medical Research Council of Australia, and Bill & Melinda Gates Foundation.